Fotografi Smartphone Dalam Penyebaran Informasi dan Sumber Belajar On Line - Rabiulza Pratama; Syarul Abidin (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2023)
The development of information and communication technology has had a major influence on the world of education. Currently, it's not just journalists who can spread the news, ordinary people can also do it with social media. This role is referred to as citizen journalism. they can assist the media in disseminating information by using Smartphones. The development of smartphone camera technology is of great benefit to the dissemination of citizen journalism information. The performance of the camera on the smartphone has good image quality. Photos have significant value because they capture moments that will never happen again. With a camera on a smartphone, everyone can become a photographer and can become a Citizen Journalist. Current photography activities do not have to have or use a professional camera, but instead make more use of smart phone cameras that are used to capture existing events and inform them on bad luck media.